Rare orchid species in Malaysia: new records, recollections and amended descriptions - Besi, Edward Entalai; Hooi, Wai Keong; Sylvester Pungga, Runi; Yong, Christina Seok Yien; Mustafa, Muskhazli; Go, Rusea (Public Library of Science, 2022)
Paphiopedilum exul, Calanthe chrysoglossoides, and Luisia brachystachys are reported here as new records for Malaysia, whereas Bryobium cordiferum subsp. borneense, Habenaria rostellifera, and Taeniophyllum rugulosum are three rare orchid species recollected from Sarawak, Perlis, and Perak, respectively. This paper highlights brief descriptions and photographic illustrations of each species for easy identification. Besides, notes on morphological comparisons with the closely related species and artificial taxonomic keys are included as well.